Students"™ Learning Needs in Critical Writing: What Do the Teachers Say? - Nugroho, Arif; Putro, Nur Hidayanto Setyo Pancoro; Syamsi, Kastam (Journal of English Education Program, 2024)
Despite the growing attention to EFL students"™ development of critical writing, research identifying their learning needs for this language skill remains more paucity of evidence. The present study aims to explore EFL teachers"™ perspectives on students"™ learning needs of critical writing course in university setting. Drawing on exploratory qualitative research, this study invites eight EFL teachers teaching critical writing course at some universities in Surakarta municipality, Indonesia. The required data are elicited using semi-structured interviews to reach in-depth understanding about the research issue. The findings yield a number of issues conveyed by the EFL teachers related to students"™ learning needs of critical writing. First, teaching critical writing plays a crucial role in shaping students"™ profile toward the twenty-first century skills. Second, a learning model of critical writing instruction, including the syllabus and plannings, learning technique and media, instructional materials, and assessment model, must be developed. As the pedagogical implication, ELT practitioners and policy makers can use this study"™s findings as references in taking policy related to teaching critical writing in university setting.